Sistem Pendukung Keputusan Supplier Terbaik Menggunakan Metode Simple Additive Weighting Pada PT.GSEI - Andriani Andriani; Muhammad Fatkhul Mutaqin; Suherman Suherman (DPPM Universitas Pelita Bangsa, 2020)
Decision Support System is basically made to facilitate decision-making in order to avoid making subjective manner. At GS ElectechIndonesia PT best supplier decision-making process in made using Simple Additive Weighting method (SAW), which consists of several criteria : criteria Benefit and criteria Cost. In building this system the author uses the method System Development Life Cycle Waterfall or waterfall method, and for design author using Unified Modeling Language (UML). For the making of the application, writer using C# programming language and the MySQL database and to test using the method of Black Box Testing. The result of this research is a decision support applications using Simple Additive Weighting Method (SAW), which is used on PT.GSEI for the best supplier selection.